Cystic Fibrosis Patient Registries: Domestic and Foreign Experience - Dmitry A. Andreev; Ekaterina E. Bashlakova; Natalia V. Khachanova; Maria V. Davydovskaia (Педиатрическая фармакология, 2017)
Cystic fibrosis is a multi-organ genetic disease that reduces life expectancy and requires costly complex therapy. The economic burden of cystic fibrosis is determined by the cost of treatment, the conditions for optimizing medical technologies based on epidemiological knowledge of the disease course nature and the therapy effectiveness. In many countries cystic fibrosis patient registries have been created that allow to assess the quality, efficiency and optimality of medical care. Registries are formed at the regional, national, and international levels, which facilitates the collection of complete and reliable patient information for subsequent analysis, comparison and synthesis of clinical and epidemiological indicators. The review is devoted to the actual principles of organization of domestic and some foreign cystic fibrosis patient registries. The article selectively provides examples of information from registries. The application of positive experience of the work of foreign registries in Russia can improve the quality of medical care for patients with cystic fibrosis.